AB0742 Pure peripheral giant cell arteritis: A systematic literature review of a poorly characterized clinical entity. (23rd January 2014) - Berti, A.; Cavalli, G.; Guglielmi, B.; Campochiaro, C.; Sabbadini, M.G.; Dagna, L.
Abstract : Background: Giant cell arteritis (GCA) is a systemic vasculitis involving large arteries tipically in the craniocervical district. Vasculitis of the aorta or of the arteries of the limbs may be present together with the classical involvement or as the sole manifestation of disease. In particular, the pure "peripheral GCA" (vasculitis of the arteries of the limbs, without aortic and cranio-cervical involvement) is an extremely rare form of GCA and its specific feature are not univocally described. Objectives: To identify clinical features, laboratory findings, and imaging features of pure peripheral GCA. Methods: We searched the English-language medical literature indexed in PubMed using the keywords ``peripheral GCA" or "extracranial GCA" or "large vessel GCA". We included in the analysis only the manuscripts univocally reporting for each patient a peripheral arteritis in the absence of aortic and craniocervical involvement. Only 79 patients described in 6 reports fulfilled those criteria. We also included in our analysis a patient recently diagnosed with pure peripheral GCA in our Department. Results: Of the 80 identified patients with pure peripheral GCA, arteries of upper limbs were involved in 86% of the patients; lower limbs arteritis was present in 8% of the patients; the remaining 6% had a simultaneous involvement of the vessels of both the upper and lower limbs. Limb claudication was the main complaint of the patients. Audible vascular bruits, asymmetric pulses and blood pressure were also a common finding. Cranial symptoms (headache of new onset, jaw claudication, visual symptoms) were not frequent (16%) and only 10% of patients had polymyalgia rheumatica. Systemic symptoms such as fever, malaise, and weight loss were also rare in those patients. The mean ESR in was 76 mm/h. The most frequently reported imaging study to define the vascular abnormality was classic angiography (70%). Our patient, who developed bilateral arteritis of the brachial arteries, had both a positive angio-MR and FDG-PET imaging. Conclusions: Pure peripheral GCA involves mostly upper limb arteries and classically manifests with limb claudication. The cranial and constitutional symptoms, as well as polymialgia rheumatica, typically seen in classic GCA are fairly uncommon. Since patients with pure peripheral GCA do not satisfy the proposed 1990 ACR classification criteria and since non-inflammatory arterial occlusive diseases must be considered in the differential diagnosis of this condition, classic vascular studies should be accompanied by more accurate techniques, able to investigate the vessel wall or its metabolic activity (such as high-definition MRI or FDG-PET). References: Brack A et al. Disease pattern in cranial and large-vessel giant cell arteritis. Arthritis Rheum 1999. Basu N et al. EULAR points to consider in the development of classification and diagnostic criteria in systemic vasculitis. Ann Rheum Dis 2010. Lie JT. Aortic and extracranial large vessel giant cell arteritis: a review of 72 cases with histopathologic documentation. Semin Arthritis Rheum 1995. Disclosure of Interest: None Declared